Modelling and optimization of hexavalent chromium removal from aqueous solution by adsorption on low-cost agricultural waste biomass using response surface methodological approach - Boutheina Rzig (IWA Publishing, 2021)
In this study, a response surface methodology (RSM) approach using central composite design (CCD) was investigated to develop a mathematical model and to optimize the effects of pH, adsorbent amount and temperature related to the hexavalent chromium removal by biosorption on peanut shells (PSh). The highest removal percentage of 30.28% was found by the predicted model under the optimum conditions (pH of 2.11, 0.73 g of PSh and 37.2 °C) for a 100 mg/L initial Cr(VI) concentration, which was very near to the experimental value (29.92%). The PSh was characterized by SEM, EDX, FTIR, BET, XRD analyses. Moreover, a Langmuir isotherm fitted well (R2 = 0.992) with the experimental data, and the maximum adsorption capacity was discovered to be 2.48 and 3.49 mg/g respectively at 25 and 45 °C. Kinetic data were well foreseen by pseudo second order. Thermodynamic study depicted that biosorption of Cr(VI) onto PSh was spontaneous and endothermic. Regeneration of the PSh using NaOH showed a loss <5% in the Cr(VI) removal efficiency up to three recycle runs. In summary, the Cr(VI) removal onto economic, sensitive and selective biosorbent (PSh) was optimized using CCD to study biosorption behaviors. HIGHLIGHTS Biosorption has been investigated as a solution for Cr(VI) removal from wastewater.; Optimization of Cr(VI) removal on PSh through 3 factors central composite design.; The highest removal yield was obtained for a pH of 2.11, adsorbent amount of 0.73 g and temperature of 37.2 °C.; The maximum adsorption capacity was 3.5 mg/g. Cr(VI) adsorption followed Langmuir isotherm and pseudo-second-order kinetic models.;